2013
DOI: 10.1007/s00198-013-2266-0
|View full text |Cite
|
Sign up to set email alerts
|

The discriminatory capacity of BMD measurements by DXA and dual X-ray and laser (DXL) at the calcaneus including clinical risk factors for detecting patients with vertebral fractures

Abstract: DXL was similarly sensitive compared with DXA for identification of subjects with vertebral fragility fractures, and combination of CRF with BMD by DXL or DXA further increased the discriminatory capacity for detection of patients susceptible to vertebral fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Calcaneal bone consists mainly of trabecular bone and its structure is comparable to that of vertebral bodies [39]. aBMD by DXL was shown to be similarly sensitive in the identification of subjects with vertebral fragility fractures when compared to DXA [20]. Significant relations between aBMD by DXL and trabecular bone microstructure assessed by HR-pQCT were also found in the present study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Calcaneal bone consists mainly of trabecular bone and its structure is comparable to that of vertebral bodies [39]. aBMD by DXL was shown to be similarly sensitive in the identification of subjects with vertebral fragility fractures when compared to DXA [20]. Significant relations between aBMD by DXL and trabecular bone microstructure assessed by HR-pQCT were also found in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies suggested that DXL reflects the actual bone status [18] and predicts hip fractures in osteoporotic women [19]. The power of DXL to identify patients with vertebral fractures was reported to be comparable to DXA at the femoral neck and superior to DXA of the lumbar spine [20].…”
Section: Introductionmentioning
confidence: 98%
“…Due to the low sensitivity of DXA, it is limited in its ability to discriminate between female and male patients with and without prevalent fractures, which was recently shown for TBS in male patients [14,24]. The predictive ability of lumbar spine texture analysis using TBS as a variable for osteoporotic fracture and a risk factor for death (independent of clinical risk factors assessed by the FRAX algorithm) was also shown for both pre-and postmenopausal women [25].…”
Section: Discussionmentioning
confidence: 94%
“…Areal lumbar spine (L1-L4) and total hip BMD were measured after daily cross calibrations by IOF_ISCD certified technicians at both investigational centers using a DXA scanner (GE LUNAR iDXA, software version Encore 13, 50,040, GE LUNAR Corporation, Madison, WI, USA). The coefficients of variation (CV) for the spine and hip were, respectively, 0.41% and 0.53% (Vienna) and 0.38% and 0.58% (Graz) [14]. Fractured vertebrae were excluded from BMD calculation.…”
Section: Trabecular Bone Score (Tbs) Measurement and Areal Bone Minermentioning
confidence: 99%
“…Prior studies assessing foot-bone density have been mostly limited to calcaneus measurements using dual X-ray and laser (DXL) [24,25] or quantitative ultrasonometry [26,27]. The calcaneus, however, is largely comprised of trabecular bone with only a thin surrounding cortical shell; therefore, any bone loss (or gain) of the calcaneus is presumably in the trabecular component of the bone and not in the cortical component of the bone.…”
Section: Discussionmentioning
confidence: 99%